2018
DOI: 10.1177/1088767918754306
|View full text |Cite
|
Sign up to set email alerts
|

Sex Work and Occupational Homicide: Analysis of a U.K. Murder Database

Abstract: This article presents an analysis of occupational homicides of sex workers in the United Kingdom, 1990Kingdom, -2016. Characteristics of 110 people murdered between 1990 and 2016 are explored including the location of their murder, ethnicity, migration status, and gender. Key changes over time are noted including an increase in the number of sex workers murdered indoors as well as an increase in murdered migrant sex workers. By developing the concept of "occupational homicide," we argue that sex worker homici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
20
0
3
Order By: Relevance
“…They described the burden of violence and called for violence against sex workers to be made a public health priority, nationally and internationally. Recent research examining UK data on sex work related homicides which compared prevalence to available data for other professions found ‘sex work is the job in the UK with the absolute greatest risk of occupational homicide for women’ (Cunningham et al ) but that indeed the trend had changed from risk being highest in the street market to now being highest for indoor workers.…”
Section: Shifting Trends: Crime Against Sex Workers and Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…They described the burden of violence and called for violence against sex workers to be made a public health priority, nationally and internationally. Recent research examining UK data on sex work related homicides which compared prevalence to available data for other professions found ‘sex work is the job in the UK with the absolute greatest risk of occupational homicide for women’ (Cunningham et al ) but that indeed the trend had changed from risk being highest in the street market to now being highest for indoor workers.…”
Section: Shifting Trends: Crime Against Sex Workers and Risk Managementmentioning
confidence: 99%
“…From our survey, threats of violence had been experienced by 12.6 per cent ( n = 81) of respondents in the last year and 25 per cent of workers during the last five years ( n = 160), while 72.9 per cent ( n = 467) had not experienced this. Sex workers are amongst the most likely group of workers to be murdered. Analysis from Sanders et al () of the UK sex worker homicide database demonstrates that there have been some dramatic changes in the composition of murders against sex workers in the past twenty years, with the trend changing from greater risk being on the street, to now more murders happening in indoor premises (see Cunningham et al ). Another alarming and notable trend is the high vulnerability of migrant sex workers, with more non‐British nationals murdered in the past decade. The most significant finding of our research was the high levels of digitally facilitated crime experienced by people in this online sector.…”
Section: Digital World Digital Crime: Online Sex Workers’ Experiencementioning
confidence: 99%
“…Commemorations are performed locally, nationally and internationally but are also often documented through websites or Twitter. For example a UKbased national charity, National Ugly Mugs, tweet out the first name, death date, and age of sex workers who are in their UK Murder Database [18]. At a local level there are various styles of commemorations and actions organised by sex worker rights groups and third sector organisations across the country.…”
Section: Background and Related Workmentioning
confidence: 99%
“…A number of other studies have also shown that sex workers are a highly targeted group of victims in serial homicide (Brewer et al, 2006; Brooks-Gordon, 2006; Egger, 2003; Kinnell, 2006; Quinet, 2011; Salfati, 2009; Salfati et al, 2008), with some work suggesting that 32% of serial homicides involve sex workers (Quinet, 2011), and that in the United States when sex worker victims are killed, in at least 35% of cases, a serial offender will be involved (Brewer et al, 2006) and that between 1990 and 2016 in the United Kingdom, 15% of all solved cases of sex worker homicides were by serial offenders (Cunningham, Sanders, Platt, Grenfell and Macioti (2018).…”
Section: Offenders Who Target Sex Workersmentioning
confidence: 99%
“…Salfati and Sorochinski (2018) reported that 45% of the series they analyzed included only sex worker victims, 42% included a mix of sex workers and non–sex workers, and another 13% included not only at least one sex worker victim but also at least one victim whose occupation was not known (i.e., they could have fallen into either of the two categories). Cunningham et al (2018), in their recent study, also pointed out that “some of the serial offenders in the United Kingdom were known only to have targeted sex workers and others had both sex working and nonsex working victims” (p. 330). These initial results all go against much of the belief in the field that offenders are behaviorally consistent and display victim preferences, especially in cases where sex workers are targeted.…”
Section: Crossover In Victim Types Among Serial Offenders Who Target mentioning
confidence: 99%